Oxytocin: Its Mechanism of Action and Receptor Signalling in the Myometrium. (June 2014) - Arrowsmith, S.; Wray, S.
<x xml:space="preserve">Abstract</x> Oxytocin is a nonapeptide hormone that has a central role in the regulation of parturition and lactation. In this review, we address oxytocin receptor (OTR) signalling and its role in the myometrium during pregnancy and in labour. The OTR belongs to the rhodopsin‐type (Class 1) of the G‐protein coupled receptor superfamily and is regulated by changes in receptor expression, receptor desensitisation and local changes in oxytocin concentration. Receptor activation triggers a number of signalling events to stimulate contraction, primarily by elevating intracellular calcium (Ca2+). This includes inositol‐tris‐phosphate‐mediated store calcium release, store‐operated Ca2+ entry and voltage‐operated Ca2+ entry. We discuss each mechanism in turn and also discuss Ca2+‐independent mechanisms such as Ca2+ sensitisation. Because oxytocin induces contraction in the myometrium, both the activation and the inhibition of its receptor have long been targets in the management of dysfunctional and preterm labours, respectively. We discuss current and novel OTR agonists and antagonists and their use and potential benefit in obstetric practice. In this regard, we highlight three clinical scenarios: dysfunctional labour, postpartum haemorrhage and preterm birth.